Tunisian Political Revolution: A Lesson Learned for Recent Indonesian Politics in Using Social Media - Fachrie, Muhammad (State Islamic Institute of Kudus (IAIN Kudus), 2020)
This research discusses about Tunisian Revolution and a lesson learned for recent Indonesian Politics. The fall of Ben Ali is a proof that social media can be a non-military weapon for society in ruining the ruling regime. Social media can create public sphere for Tunisian people in communicating each other, sharing information and even mobilizing the protest over Ben Ali’s regime. This experience gives lesson learned for many country, including Indonesia. Recently, Indonesian people are active in internet, particularly social media, so that Tunisian Revolution experience alerts Indonesian people to always pay attention about that. This research uses qualitative method to gather data and describe the phenomenon by using Critical Theory. This research views that Tunisian experience influences to the government in managing protests in Indonesia, because the policy and regulation about internet and social media occur in Joko Widodo’s administration in order to counter hoaxes, SARA and radicalism.